NiCo/NiCo–OH and NiFe/NiFe–OH core shell nanostructures for water splitting electrocatalysis at large currents - Zhu, Weijie; Chen, Weixin; Yu, Huanhuan; Zeng, Ye; Ming, Fangwang; Liang, Hanfeng; Wang, Zhoucheng (Applied catalysis. B, Environmental, 2020)
[Display omitted] Core-shell bimetallic alloy/oxyhydroxide electrocatalyst can stably drive the water splitting electrocatalysis at 1000 mA cm−2 for 300 h without significant performance decay. •Alloy/(oxy)hydroxide electrodes were designed by a rapid electrodeposition method.•The core-shell heterostructure exposes abundant active sites and accelerates the charge transfer.•The device can steadily catalyze water splitting at 1 A cm−2 for at least 300 h. A big challenge in practical water splitting is the sluggish reaction kinetics at high current densities that essentially requires efficient electrocatalysts to lower the overpotentials. While exciting progress has been made in noble metal-based catalysts, earth-abundant materials that can actively catalyze the water splitting at high current densities (e.g. ≥500 mA cm−2) are rare. In this work, we show that a rational design of the catalysts could promote the charge transfer, facilitate the gas release, as well as boost the surface active sites, and therefore significantly enhance the electrocatalytic activity toward both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Using NiCo/NiCo−OH and NiFe/NiFe−OH as examples, we achieved ultralow overpotentials of 184 and 296 mV at 500 mA cm−2 in 1M KOH for HER and OER, respectively. More importantly, the alkaline electrolyzer based on these two materials is able to actively drive the overall water splitting at 1000 mA cm−2 for at least 300 h at a low cell voltage without significant performance decay, which is much superior to the state-of-the-art 20 % Pt/C||RuO2 combination. Our work points out a promising pathway to achieve inexpensive electrocatalysts for practical water splitting at high currents.